Effect of TGase Crosslinking on the Structure, Emulsification, and Gelling Properties of Soy Isolate Proteins - Ziqi Peng; Kunlun Liu; Ning Liao (Foods)
Soy isolate protein (SPI), as a high-quality plant protein source, is often processed into various soy products. In this study, the physicochemical properties of SPI treated with transglutaminase (TGase) were investigated in correlation with emulsification characteristics and rheological behavior. The polyacrylamide gel electrophoresis with sodium dodecyl sulfate (SDS-PAGE) and Fourier-transform infrared spectroscopy (FTIR) and endogenous fluorescence spectrum analysis results showed that TGase was able to promote the covalent binding of lysine and glutamine residues in SPI. The moderate pre-crosslinking treatment of TGase (5–7.5 U/g TGase pre-crosslinked for 2 h or 5 U/g TGase pre-crosslinked for 2–3 h) improved the emulsification and gel properties to varying degrees: the nanoparticle and emulsification performance increased by 24.35% and the storage modulus of the gel increased by 288%. Furthermore, the surface charge of SPI increased due to the crosslinking impact of TGase, indicating a considerable rise in the surface electrostatic potential. Simultaneously, the protein surface exhibited a substantial increase in hydrophobicity, while the level of free sulfhydryl groups reduced. These changes indicate that TGase enzymatic crosslinking could significantly improve the structural stability of nanoparticles by enhancing the generation efficiency of covalent bonds between protein molecules.